2021
DOI: 10.3390/biology10121353
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Soybean Hairy Root Construction and Its Application in the Soybean—Nematode Interaction: An Investigation

Abstract: Background: The yield of soybean is limited by the soybean cyst nematode (SCN, Heterodera glycines). Soybean transformation plays a key role in gene function research but the stable genetic transformation of soybean usually takes half a year. Methods: Here, we constructed a vector, pNI-GmUbi, in an Agrobacterium rhizogenes-mediated soybean hypocotyl transformation to induce fluorescent hairy roots (FHRs). Results: We describe the operation of FHR-SCN, a fast, efficient and visual operation pathosystem to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Rockwool inoculation, Agrobacterium dipping, and Agrobacterium injection are three applicable in planta techniques; however, Agrobacterium injection is the most prevalent method. Hypocotyl and/or the cotyledonary node are the most used tissues for in planta hairy root induction in soybean [37]. Most in planta A. rhizogenes studies in soybean are based on the protocol reported by Kereszt et al [32].…”
Section: Hairy Root Transformationmentioning
confidence: 99%
“…Rockwool inoculation, Agrobacterium dipping, and Agrobacterium injection are three applicable in planta techniques; however, Agrobacterium injection is the most prevalent method. Hypocotyl and/or the cotyledonary node are the most used tissues for in planta hairy root induction in soybean [37]. Most in planta A. rhizogenes studies in soybean are based on the protocol reported by Kereszt et al [32].…”
Section: Hairy Root Transformationmentioning
confidence: 99%